Respuesta :

Neuron
If you would like to solve the system of equations, you can do this using the following steps:

y = 2/3x + 2
6x - 4y = -10
___________
6x - 4y = -10
6x - 4 * (2/3x + 2) = -10
6x - 8/3x - 8 = -10
6x - 8/3x = -10 + 8      /*3
18x - 8x = -2 * 3
10x = -6
x = -6/10
x = -3/5

y = 2/3x + 2 = 2/3 * (-3/5) + 2 = - 2/5 + 2 = - 2/5 + 10/5 = 8/5

(x, y) = (-3/5, 8/5)

The correct result would be: one solution; 
(-3/5, 8/5).

Answer:

The answer is b one solution-0.6, 1.6

Step-by-step explanation:

truss me

ACCESS MORE